Methods of the Detection of Parasite Infections in Libya- A Review (Journal of Academic Research, 2020)
Diagnosis of parasitic diseases requires highly sensitive and specific tests. In many cases the identification of parasites concerns their epidemiology and it is important to distinguish between species and subspecies. The current laboratory tests practiced in Libya are based on conventional techniques including serology and microscopy. More rapid and accurate tests are needed to meet the increasing number of patients in Libya. Nowadays, advanced methods are used to improve the diagnosis of parasitic diseases. These include molecular-based techniques such as polymerase chain reaction (PCR). The principle of nucleic acid probes is that a specific sequence of the parasite's DNA is isolated and used in a hybridization assay to identify homologous parasite DNA from infected material. Since DNA normally remains the same during every stage of the parasite's life cycle, this technique has many applications. The effective control and treatment of parasitic diseases requires rapid, reliable and highly sensitive diagnostic test. This review summarizes both the conventional methods and the progress in new approaches in parasite diagnoses, and debates some of the merits and demerits of these tests.